Efficacy and Safety Comparison between Empagliflozin and Linagliptin among Type 2 Diabetes Mellitus Patients : A Systematic Review and Meta-Analysis - Harzalina Zilfi Amly; Evi Ananta Ulisa Sitepu; Igna Laurensus Sitorus (Jurnal Ilmu Multidisiplin, 2025)
Introduction: Empagliflozin and linagliptin are two commonly used medications for the management of Type 2 Diabetes Mellitus (T2DM). However, direct comparison of their efficacy and safety profiles remains limited. This study aims to compare efficacy and safety of empagliflozin and linagliptin in T2DM patients. Methods: Systematic review was done according to the PRISMA statements. Searching was conducted among multiple databases with specific keywords. Selection of studies were done by set of inclusion and exclusion criteria. Included studies were appraised using the Cochrane RoB2.0 critical appraisal tools. Analysis was done qualitatively and quantitatively, with assistance of RevMan 5.4. Heterogeneity analysis was done to determine the effects model used. P value of <0.05 was determined as statistical significance. Results: Four studies with low risk of bias and involving 420 subjects were included. Analysis showed that empagliflozin resulted in significantly greater reductions in HbA1c (MD = 0.71%, 95% CI = 0.43–0.99%) and fasting blood glucose (MD = 47.61 mg/dl, 95% CI = 25.57–69.65 mg/dl) compared to linagliptin. In terms of safety, there were no significant differences in the incidence of hypoglycemia (OR = 0.73, 95% CI = 0.38–1.38) or urinary tract infections (OR = 0.68, 95% CI = 0.37–1.25) between the two treatments. Conclusion: Empagliflozin provided better glycemic control over linagliptin among T2DM patients with satisfactory safety profile.